Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How can I calculate the following sum involving binomial terms:

$$\sum_{k=0}^{n} \binom{n}{k}\frac{(-1)^k}{(k+1)^2}$$

Where the value of n can get very big (thus calculating the binomial coefficients is not feasible).

Is there a closed form for this summation?

share|cite|improve this question
Wolfram has a suggestion, which is beyond my comprehension. – Hendrik Jan Dec 9 '12 at 10:26
The same answer with maple $\frac{\psi(n+2)+\gamma}{n+2}$. – Mhenni Benghorbal Dec 9 '12 at 10:57
@Michael: can you add (as a one-liner) in what context you found the question? Just curious. – Hendrik Jan Dec 9 '12 at 16:21
up vote 11 down vote accepted

Apparently I'm a little late to the party, but my answer has a punchline!

We have $$ \frac{1}{z} \int_0^z \sum_{k=0}^{n} \binom{n}{k} s^k\,ds = \sum_{k=0}^{n} \binom{n}{k} \frac{z^k}{k+1}, $$ so that $$ - \int_0^z \frac{1}{t} \int_0^t \sum_{k=0}^{n} \binom{n}{k} s^k\,ds\,dt = - \sum_{k=0}^{n} \binom{n}{k} \frac{z^{k+1}}{(k+1)^2}. $$ Setting $z = -1$ gives an expression for your sum, $$ \sum_{k=0}^{n} \binom{n}{k} \frac{(-1)^k}{(k+1)^2} = \int_{-1}^{0} \frac{1}{t} \int_0^t \sum_{k=0}^{n} \binom{n}{k} s^k\,ds\,dt. $$ Now, $\sum_{k=0}^{n} \binom{n}{k} s^k = (1+s)^n$, so $$ \begin{align*} \sum_{k=0}^{n} \binom{n}{k} \frac{(-1)^k}{(k+1)^2} &= \int_{-1}^{0} \frac{1}{t} \int_0^t (1+s)^n \,ds\,dt \\ &= \frac{1}{n+1}\int_{-1}^{0} \frac{1}{t} \left[(1+t)^{n+1} - 1\right]\,dt \\ &= \frac{1}{n+1}\int_{0}^{1} \frac{u^{n+1}-1}{u-1}\,du \\ &= \frac{1}{n+1}\int_0^1 \sum_{k=0}^{n} u^k \,du \\ &= \frac{1}{n+1}\sum_{k=1}^{n+1} \frac{1}{k} \\ &= \frac{H_{n+1}}{n+1}, \end{align*} $$ where $H_n$ is the $n^{\text{th}}$ harmonic number.

share|cite|improve this answer
+1: This is definitely the best answer – Amr Dec 9 '12 at 11:11
You are absolutely right Antonio, I just got to the same expression using the fact $\sum \binom{n}{k}\frac{(-1)^k}{x+k} = x^{-1}\binom{x+n}{n}^{-1}$ and taking the derivative on both sides. – Michael Dec 9 '12 at 11:26
Just to confirm your answer with the others in the comment, here is the relation between the $\psi$ function and the harmonic numbers $ H_n=\gamma+\psi_0(n+1)$. See here. – Mhenni Benghorbal Dec 9 '12 at 14:21

I'm even later to the party, but that's only because "absorption identity" kept yelling in my ear. :)

One application of the absorption identity gets one of the factors of $k+1$ out of the denominator: $$\begin{align} \sum_{k=0}^n \binom{n}{k} \frac{(-1)^k}{(k+1)^2} &= \frac{1}{n+1} \sum_{k=0}^n \binom{n+1}{k+1} \frac{(-1)^k}{k+1} \\ &= \frac{1}{n+1} \sum_{k=1}^{n+1} \binom{n+1}{k} \frac{(-1)^{k+1}}{k} \end{align}.$$ It would be nice to use the absorption identity again, but we need a $k+1$ in the denominator of the summand rather than a $k$. By using the basic binomial coefficient recursion formula, we can make that happen.

Let $\displaystyle f(n) = \sum_{k=1}^{n} \binom{n}{k} \frac{(-1)^{k+1}}{k}.$ Then looking at the difference of $f(n+1)$ and $f(n)$ gives us $$\begin{align} f(n+1) - f(n) &= \sum_{k=1}^{n+1} \binom{n+1}{k} \frac{(-1)^{k+1}}{k} - \sum_{k=1}^n \binom{n}{k} \frac{(-1)^{k+1}}{k} \\ &= \sum_{k=1}^{n+1} \binom{n}{k-1} \frac{(-1)^{k+1}}{k} \\ &= \sum_{k=0}^n \binom{n}{k} \frac{(-1)^{k}}{k+1} \\ &= \frac{1}{n+1}\sum_{k=0}^n \binom{n+1}{k+1} (-1)^{k} \:\:\:\: \text{ (absorption identity!)} \\ &= \frac{1}{n+1} \left(1 + \sum_{k=0}^{n+1} \binom{n+1}{k} (-1)^{k+1} \right)\\ &= \frac{1}{n+1}, \end{align}$$ where in the last step we used the fact that the alternating sum of the binomial coefficients is $0$.

Thus $$f(n+1) = \sum_{k=0}^n (f(k+1) - f(k)) = \sum_{k=0}^n \frac{1}{k+1} = H_{n+1}.$$

Therefore, $$\sum_{k=0}^n \binom{n}{k} \frac{(-1)^k}{(k+1)^2} = \frac{H_{n+1}}{n+1}.$$

share|cite|improve this answer

$(1-x)^n=\sum_{0\le k\le n}\binom nk(-1)^kx^k$

Integrating wrt $x,$

$$-\frac{(1-x)^{n+1}}{n+1}+C=\sum_{0\le k\le n}\binom nk(-1)^k\frac{x^{k+1}}{k+1}$$ where $C$ is the indefinite constant.

Putting $x=0,C-\frac1{n+1}=0\implies C=\frac1{n+1}$

So, $$\sum_{0\le k\le n}\binom nk(-1)^k\frac{x^{k+1}}{k+1}=\frac1{n+1}-\frac{(1-x)^{n+1}}{n+1}$$

So, $$\sum_{0\le k\le n}\binom nk(-1)^k\frac{x^{k}}{k+1}=\frac1{x(n+1)}-\frac{(1-x)^{n+1}}{(n+1)x}$$

Again integrating wrt $x,$

$$\sum_{0\le k\le n}\binom nk(-1)^k\frac{x^{k+1}}{(k+1)^2}=\frac {\log x}{n+1}-\int\frac{(1-x)^{n+1}}{(n+1)x}dx+D$$ where $D$ is the indefinite constant.

share|cite|improve this answer
you have missed all the binomial coefficients here – dexter04 Dec 9 '12 at 11:00
The integration of $x^{k+1}/k+1$ is $x^{k+2}/(k+1)(k+2)$ – Amr Dec 9 '12 at 11:03
Thanks, rectified the errors. – lab bhattacharjee Dec 9 '12 at 11:30

I don't if you would accept this:

$$$\sum_{k=0}^{n} \binom{n}{k}x^k=(1+x)^k$$

Integrate with respect to $x$ from $0$ to $t$ to get: $$\sum_{k=0}^{n} \binom{n}{k}\frac{t^{k+1}}{k+1}=\frac{(1+t)^{k+1}-1}{k+1}$$

Now divide by $t$ to get: $$\sum_{k=0}^{n} \binom{n}{k}\frac{t^{k}}{k+1}=\frac{(1+t)^{k+1}-1}{(k+1)t}$$

Now interate agian with respect to $t$ from $0$ to $z$ to get:

$$\sum_{k=0}^{n} \binom{n}{k}\frac{z^{k}}{(k+1)^2}=\int_{0}^z\frac{(1+t)^{k+1}-1}{(k+1)t}dt$$ Now Let $z=-1$ $$\sum_{k=0}^{n} \binom{n}{k}\frac{(-1)^{k}}{(k+1)^2}=\int_{0}^{-1}\frac{(1+t)^{k+1}-1}{(k+1)t}dt$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.